Self-esteem, Gender, Family-communication-style and Parental Neglect as Predictors of Aggresive Tendencies among Secondary School Adolescents - Henry Odhianosen Imhonde (International Journal of Public Health Science (IJPHS), 2013)
ABSTRACTThis study examined the role of Self-esteem, Gender, family communication style, and Parental neglect on aggressive tendencies among secondary school adolescents’ in Esan West Local Government Area of Edo State. A total of two hundred and forty (240) secondary school adolescents drawn from 9 private and 3 public schools in Esan West Local government Area of Edo state participated in the study.  One hundred and forty of the participants were males, while one hundred were females. A questionnaire was used in collecting data. The questionnaire consisted of five sections; the demographic variables, Family communication style, Parental neglect, Self-esteem, and Aggressive tendencies. Results of the multiple regression analysis revealed that only self-esteem, independently predict aggressive tendencies. Family communication style, gender and parental neglect were not found to independently predict aggressive tendencies. However, self-esteem, gender, family communication, parental neglect jointly predict aggressive tendencies among secondary school adolescents. Based on the findings of this study, it is recommended that the future of a successful intervention by therapist/service providers for students with aggressive behaviour in Nigeria lies heavily on knowing and identifying the personal and family characteristics of the individual. This no doubt would help the therapists in managing individuals with specific treatment.DOI: http://dx.doi.org/10.11591/ijphs.v2i3.2873